Linguistic and Cultural Analysis of Positive and Negative Emotions in Uzbek and English - Xayrullayeva , Shaxzoda (The Lingua Spectrum, 2025)
This study examines the linguistic and cultural expression of positive and negative emotions in Uzbek and English, focusing on how grammatical structures, lexical choices, and cultural norms shape emotional communication. The research reveals key differences: Uzbek favors emotional restraint, especially in public, using verb phrases and adjectives, while English allows more flexibility, utilizing auxiliary verbs and adjectives for a wider emotional range. Both languages employ metaphor and figurative language to convey emotions such as happiness and anger. The study highlights the influence of cultural contexts, with Uzbek prioritizing collectivism and emotional control, and English valuing individual expression and autonomy. The findings provide insights into how language and culture interact to shape emotional experiences, offering valuable perspectives for cross-cultural communication and understanding.